REGIONAL TECHNOLOGY-RELATED THREATS FOR NATIONAL SAFETY OF UKRAINE - Баталов, О.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
It has been determined that pollution of environment threatens the national safety, not only through worsening the level of people life, but also resulting in environmentally reasonable protests. The main technology related threats, existing in 27 regions of Ukraine within the last five years, have been analyzed on such parameters as: dynamics of atmospheric air pollution, dynamics of discharge of waste water to surface water objects, dynamics of accumulation of wastes of I-III class of hazard, dynamics of increase/decrease of site areas for solid municipal waste, endangering the national (environmental) safety of Ukraine. A “rifle approach” has been offered to rectify the indicated threats.